WHO Global Consultation on Public Health Intervention against Early Childhood Caries. Issue 3 (30th January 2018) - Phantumvanit, Prathip; Makino, Yuka; Ogawa, Hiroshi; Rugg‐Gunn, Andrew; Moynihan, Paula; Petersen, Poul Erik; Evans, Wendell; Feldens, Carlos Alberto; Lo, Edward; Khoshnevisan, Mohammad H.; Baez, Ramon; Varenne, Benoit; et al.
Abstract: Early Childhood Caries (ECC) is prevalent around the world, but in particular the disease is growing rapidly in low‐ and middle‐income countries in parallel with changing diet and lifestyles. In many countries, ECC is often left untreated, a condition which leads to pain and adversely affects general health, growth and development, and quality of life of children, their families and their communities. Importantly, ECC is also a global public health burden, medically, socially and economically. In many countries, a substantial number of children require general anaesthesia for the treatment of caries in their primary teeth (usually extractions), and this has considerable cost and social implications. A WHO Global Consultation with oral health experts on "Public Health Intervention against Early Childhood Caries" was held on 26‐28 January 2016 in Bangkok (Thailand) to identify public health solutions and to highlight their applicability to low‐ and middle‐income countries. After a 3‐day consultation, participants agreed on specific recommendations for further action. National health authorities should develop strategies and implement interventions aimed at preventing and controlling ECC. These should align with existing international initiatives such as the Sixtieth World Health Assembly Resolution WHA 60.17 Oral health: action plan for promotion and integrated disease prevention, WHO Guideline on Sugars and WHO breastfeeding recommendation. ECC prevention and control interventions should be integrated into existing primary healthcare systems. WHO public health principles must be considered when tackling the effect of social determinants in ECC. Initiatives aimed at modifying behaviour should focus on families and communities. The involvement of communities in health promotion, and population‐directed and individual fluoride administration for the prevention and control of ECC is essential. Surveillance and research, including cost‐effectiveness studies, should be conducted to evaluate interventions aimed at preventing ECC in different population groups.